Mechanism of activation of porcine dendritic cells by an α-D-glucan nanoparticle adjuvant and a nanoparticle/poly(I:C) combination adjuvant - Hernandez-Franco, Juan F.; Xie, Shaojun; Thimmapuram, Jyothi; Ragland, Darryl; HogenEsch, Harm (Frontiers in Immunology, 2022)
Recent studies have shown that corn-derived cationic α-D-glucan nanoparticles, known as Nano-11, significantly increase the immune response when used as a vaccine adjuvant in mice and in pigs. Furthermore, the nanoparticles can be formulated with other immunostimulators such as poly(I:C), which further enhances the immune response. The current experiments were aimed at elucidating the mechanism of action of Nano-11 alone and in combination with poly(I:C). The effect of these adjuvants on porcine monocyte-derived dendritic cells (Mo-DCs) was determined by RNA-sequencing, supplemented with flow cytometry, cytokine analysis, and Western blots. Adsorption of poly(I:C) to Nano-11 reduced its cytotoxicity for Mo-DCs. Exposure of Mo-DCs to Nano-11 and Nano-11/poly(I:C) induced differential expression of 979 and 2016 genes, respectively. Gene Ontology enrichment and KEGG pathway analysis revealed many changes in gene expression related to inflammation, innate immunity, immune response to infections, and metabolism. Nano-11 and Nano-11/poly(I:C) induced maturation of the Mo-DCs as indicated by increased expression of costimulatory molecules and MHC II. Increased expression of genes downstream of p38 MAPK activation revealed a role for this signaling pathway in the activation of Mo-DCs by the adjuvants. This was confirmed by Western blot and inhibition of TNF-secretion upon incubation with the p38 inhibitor SB203580. These experiments provide insights into the mechanism of action of the novel adjuvants Nano-11 and Nano-11/poly(I:C).